Application of the water cascade analysis technique for water minimisation in a paper mill plant - Abdul Manan, Zainuddin; Yin, Ling Tan; Foo, Dominic Chwan Yee; Swee, Yin Tea (Inderscience Enterprises Limited, Geneva, 2007)
The Water Cascade Analysis (WCA) technique was used to identify opportunities for reduction in freshwater usage as well as wastewater generation and to assist in the retrofit of an existing paper mill water distribution network. This procedure involves three key steps; i.e., a global analysis of the present water distribution and consumption, setting the baseline minimum water targets using WCA technique and retrofit of water network to achieve the minimum water targets. Notwithstanding the extensive water recycling currently employed in the paper mill, this study identified a potential scope of reducing 13.3% freshwater and 13.3% wastewater. Water reduction represents a total potential annual savings of RM 595,232, taking into account the raw water and wastewater treatment costs, pumping and chemical costs.